2017
DOI: 10.1016/j.taap.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Acute lung injury and persistent small airway disease in a rabbit model of chlorine inhalation

Abstract: Chlorine is a pulmonary toxicant to which humans can be exposed through accidents or intentional releases. Acute effects of chlorine inhalation in humans and animal models have been well characterized, but less is known about persistent effects of acute, high-level chlorine exposures. In particular, animal models that reproduce the long-term effects suggested to occur in humans are lacking. Here, we report the development of a rabbit model in which both acute and persistent effects of chlorine inhalation can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…Individuals and animals exposed to these toxic gases may develop noncardiogenic pulmonary edema and also significant myocardial injury within hours to days of exposure (23,55). Those that survive often suffer from residual chronic lung disease, with airflow obstruction, fibrosis, airway hyper-reactivity, and impaired gas exchange (57)(58)(59)(60). In our study, the histological examination of mouse lungs after halogen exposure showed evidence of airway fibrosis, alveolar Figure 6.…”
Section: Discussionsupporting
confidence: 49%
“…Individuals and animals exposed to these toxic gases may develop noncardiogenic pulmonary edema and also significant myocardial injury within hours to days of exposure (23,55). Those that survive often suffer from residual chronic lung disease, with airflow obstruction, fibrosis, airway hyper-reactivity, and impaired gas exchange (57)(58)(59)(60). In our study, the histological examination of mouse lungs after halogen exposure showed evidence of airway fibrosis, alveolar Figure 6.…”
Section: Discussionsupporting
confidence: 49%
“…102 Animals exposed to chlorine develop pulmonary edema and alveolar inflammation characterized by neutrophil recruitment and the appearance of foamy macrophages, alveolar damage with epithelial barrier dysfunction, capillary microthrombi, and fibrin deposition. [103][104][105][106] Similarly, inhalation of high doses of chlorine results in human ALI characterized by pneumonitis, pulmonary edema, and decrements in lung function. 102 Animal exposure models suggest that much of the damage induced by chlorine can be attributed to oxidative stress.…”
Section: Chemical Threat Agent-induced Alimentioning
confidence: 99%
“…Indeed, until the Romanenko et al 184 article, there was no comparative analysis available between the karyotype of man and that of the guinea pig. In consequence, rodent models such as the mouse [185][186][187][188][189][190][191] and rat 106,[192][193][194][195] and other species such as the rabbit 196,197 have featured prominently in studies on the toxicology of chlorine exposure.…”
Section: Endogenous Trpa1 Agonistsmentioning
confidence: 99%